(untitled) (Laisvalaikio tyrimai, 2023)
Relevance of the topic. The article sets out to explore the potential of innovative analytical and statistical technologies in monitoring, detecting, and counteracting corruption within state systems. The central objective is to clarify key concepts, determine the nature and content of these technologies, and analyse their applications in anti-corruption efforts. The research methodology combines the scrutiny of official documents, legislations, public authority websites, and software providers with a focus on their anti-corruption capabilities. The study reveals that analytical and statistical technologies constitute a specific form of information technology, embodied in functional information systems that fulfil organisational objectives and assist in decision-making processes. They assist primarily in the identification and prediction of probable cases of corruption or fraudulent activities, utilising mathematical methods and advanced analytical algorithms. Key areas where these technologies can significantly contribute include data collection and processing, communication and office processes, general management processes, decision-making processes, and expert systems development. The problem. Corruption remains one of the largest socio-economic issues affecting a country’s development and undermining citizens’ trust in governing structures. Innovative analytical and statistical technologies such as artificial intelligence, machine learning, big data analysis, and others, hold the potential to provide effective monitoring and detection of corrupt schemes. The purpose of this article is to determine the directions for implementing innovative analytical and statistical technologies as a tool for monitoring, detecting and counteracting corruption in the state. Research object: Application of innovative analytical and statistical technologies in the fight against corruption. The results. Innovative analytical and statistical technology is a type of information technology, which is embodied in the form of a functional information system aimed to fulfil organisational objectives and assist in decision-making processes. These technologies are considered essential tools for countering corruption at the state level, primarily by identifying and predicting probable cases. The application of mathematical methods and advanced analytical and statistical algorithms can reveal inconsistencies and potential corruption or fraudulent activities. Counteracting corruption has also benefitted from advancements in information technologies. Currently, efforts to counter corruption focus on digital government services, crowdsourcing platforms, transparency portals, big data, and artificial intelligence. In this context, there are five key areas where analytical and statistical technologies can contribute: data collection and processing, communication and office processes, general management processes, decision-making processes, and the development of expert systems. Keywords: corruption counteraction, artificial intelligence, machine learning, information